Shift in the submucosal microbiome of diseased peri-implant sites after non-surgical mechanical debridement treatment - Sun, Fei; Wei, Yiping; Li, Siqi; Nie, Yong; Wang, Cui; Hu, Wenjie (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives: The object of this prospective study was to assess the submucosal microbiome shifts in diseased peri-implant sites after non-surgical mechanical debridement therapy. Materials and methods: Submucosal plaques were collected from 14 healthy implants and 42 diseased implants before and eight weeks after treatment. Mechanical debridement was conducted using titanium curettes, followed by irrigation with 0.2% (w/v) chlorhexidine. The 16SrRNA gene sequencing was used to analyze the shift in the submucosal microbiome before and after non-surgical treatment. Results: Clinical parameters and submucosal microbiome were statistically comparable before and after mechanical debridement. Alpha diversity was significantly decreased after mechanical debridement. However, there were still differences in richness between the post-treatment and healthy groups. In network analysis, post-treatment increased the complexity of the network compared to pre-treatment. The relative abundances of some pathogenic species, such as Porphyromonas gingivalis, Tannerella forsythia, Peptostreptococcaceae XIG-6 nodatum, Filifactor alocis, Porphyromonas endodontalis, TM7 sp., and Desulfobulbus sp. HMT 041 levels significantly decreased after nonsurgical treatment. Conclusions: Nonsurgical treatment for peri-implant diseases using mechanical debridement could provide clinical and microbiological benefits. The microbial community profile tended to shift towards healthy communities, and submucosal dysbiosis was relieved as a result of mechanical debridement..